New Arabidopsis recombinant inbred lines (Landsberg erecta x Nossen) reveal natural variation in phytochrome-mediated responses - Alconada Magliano, Teresa M. (2005)
We used 52 Arabidopsis (Arabidopsis thaliana) accessions and developed a new set of 137 recombinant inbred lines between Landsberg erecta (Ler) and Nossen (No-0) to explore the genetic basis of phytochrome-mediated responses during deetiolation. Unexpectedly, most accessions showed weak or moderate hypocotyl growth and cotyledon unfolding responses to pulses of far-red light (FR). Crosses between Columbia and No-0, two accessions with poor response, segregated seedlings with unfolded cotyledons under pulsed FR, suggesting the occurrence of accession-specific loci in the repression of morphological responses to weak light signals. Confirming the latter expectation, mapping of responses to pulsed FR in the Ler x No-0 lines identified novel loci. Despite its weak response to pulsed FR, No-0 showed a response to continuous FR stronger than that observed in Ler. By mapping the differential effect of pulsed versus continuous FR, we identified two high-irradiance response loci that account for the steeper response to continuous FR in No-0. This underscores the potential of the methodology to identify loci involved in the regulation of the shape of signal input-output relationships. Loci specific for a given phytochrome-mediated response were more frequent than pleiotropic loci. Segregation of these specific loci is predicted to yield different combinations of seedling responsivity to light. Such flexibility in combination of responses is observed among accessions and could aid in the adjustment to different microenvironments.